2017
DOI: 10.3389/fmicb.2017.01716
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination in Protozoan Parasites and Recombinase Inhibitors

Abstract: Homologous recombination (HR) is a DNA double-strand break (DSB) repair pathway that utilizes a homologous template to fully repair the damaged DNA. HR is critical to maintain genome stability and to ensure genetic diversity during meiosis. A specialized class of enzymes known as recombinases facilitate the exchange of genetic information between sister chromatids or homologous chromosomes with the help of numerous protein accessory factors. The majority of the HR machinery is highly conserved among eukaryotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…However, although the length of the target sequence should be sufficient to ensure targeted cleavage even in large genomes (∼3Gb), numerous studies have reported that Cas9 can induce off-target mutations, even at sequences that differ by 5 nt from the targeted site ( 11 , 39 , 40 ). Given the absence of an NHEJ pathway in T. brucei ( 13 ) and findings using the meganuclease I- SceI in T. brucei ( 14 ), we expect that cleavage at off-target sites, for which no repair template is provided, will not be repaired efficiently and will result in cell death rather than in unintended editing events. Nevertheless, to assess the degree of off-target mutations in T. brucei , we sequenced gDNA from wild type cells and a population of cells edited using the sgRNA-episome(SCD6-GFP.1) to 21.3x and 22.9x coverage, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although the length of the target sequence should be sufficient to ensure targeted cleavage even in large genomes (∼3Gb), numerous studies have reported that Cas9 can induce off-target mutations, even at sequences that differ by 5 nt from the targeted site ( 11 , 39 , 40 ). Given the absence of an NHEJ pathway in T. brucei ( 13 ) and findings using the meganuclease I- SceI in T. brucei ( 14 ), we expect that cleavage at off-target sites, for which no repair template is provided, will not be repaired efficiently and will result in cell death rather than in unintended editing events. Nevertheless, to assess the degree of off-target mutations in T. brucei , we sequenced gDNA from wild type cells and a population of cells edited using the sgRNA-episome(SCD6-GFP.1) to 21.3x and 22.9x coverage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, while Cas9 has been successfully used to disrupt multicopy genes via repair through NHEJ, it has not been used for the precise editing of large multicopy gene arrays. Many protozoa, including the medically relevant parasites Trypanosoma brucei and Trypanosoma cruzi , the causative agents of sleeping sickness and Chagas disease, have very inefficient NHEJ and microhomology-mediated pathways ( 13 ). For T. brucei it was observed that in the absence of a repair template the majority of DSBs will result in cell death rather than repair by NHEJ or microhomology ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…DSB can be repaired by two main mechanisms: nonhomologous end joining (NHEJ) and homologous recombination repair (HRR); the first is an error-prone mechanism available along the cell cycle, and the second is an error-free mechanism active at S/G2 phases of cell cycle because of the requirement of sister chromatid as template [131][132][133][134]. Both mechanisms were described in T. gondii [14,135], but Plasmodium genus is thought to rely only on HRR [136][137][138].…”
Section: Double-strand Break Repair: H2ax and Chromatinmentioning
confidence: 99%
“…This phenomenon, in which short DNA patches are duplicated from a donor to a recipient gene, typically occurs without modification of the donor and at least superficially resembles HR-mediated DNA repair. DNA repair in apicomplexan and other protozoal parasites overall is not well understood [35,36]. It is even difficult to predict from the parasites' proteomes which repair pathways may be active.…”
Section: Discussionmentioning
confidence: 99%